Reductively-labile sulfonate ester protecting groups that are rapidly cleaved by physiological glutathione - Choi, Adam (Org Biomol Chem, 2017)
Sulfonates are frequently used to endow water solubility on hydrophobic molecules, but the repertoire of sulfonate protecting groups remains limited. Here we describe the first sulfonate esters that can be unmasked by the mild reducing conditions found in live mammalian cells. Self-immolative cleavage releases the sulfonate and the two-electron reduction product of a thioquinone methide.